Evaluasi Kesesuaian Kawasan Mangrove Sebagai Ekowisata di Desa Juru Seberang, Tanjungpandan, Belitung - Abdi, Nugraha Rangga; Ananto, Aji; Suroso, Suroso (Geo-Image, 2018)
This study aims to: 1) Know the level of conformity of mangrove area for ecotourism object in Desa Juru Seberang, Tanjungpandan, Belitung; 2) To know the attitude of the community to the development plan of mangrove ecotourism in Desa Juru Seberang, Tanjungpandan, Belitung. This research is descriptive qualitative research. Data analysis technique using scoring method. Based on calculation of conformity index of ecotourism area of mangrove area I with percentage 94,31% (S1), area II with percentage 81,81% (S1) and region III with percentage 78,40% (S2). Mangrove area in region I is very suitable to be or developed as an object of ecotourism. Therefore, based on the 7 parameters of the suitability of the area for the development of mangrove ecotourism (Yulianda, 2007), the highest percentage of the percentage index is found in area 1, ie in plot 1 with 94.31%. Figures obtained in the calculation mode is 31.39 entered in the class of agreed intervals (30.7-37.8) so that it can be concluded the attitude of Desa Juru Seberang is agree (S) to mangrove ecotourism.